(untitled) (Bulletin of criminological association of Ukraine, 2024)
The article analyzed the impact of the COVID-19 coronavirus pandemic on the functioning of society, changing social priorities and profound transformation of public administration, business and everyday life of people. The social nature of the changes generated by the pandemic and their impact on public authorities was studied. Attention was focused on the fact that approaches to organizing the activities of public authorities in the conditions of quarantine and anti-epidemic measures largely originate from solutions that have previously been tested and successfully proven themselves in the business sphere. It was noted that in public authorities, approaches to digitalization and distancing of everyday processes tested in business have found their embodiment in the course of applying the legal provisions of Articles 18, 22 of the Law of Ukraine “On Citizens’ Appeals” in quarantine conditions, considering the reduction of personal contact, the introduction of electronic document flow and observance of social distance. It is argued that in the inherently critical conditions of the introduction of quarantine and anti-epidemic measures, an organizational and managerial basis was developed for the transition of public authorities to remote work.